New aspects on the hepatoprotective potential associated with the antioxidant, hypocholesterolemic and anti-inflammatory activities of Vernonia condensata Baker. (23rd February 2017) - Silva, Jucélia Barbosa da; Mendes, Renata de Freitas; Tomasco, Vívian; Pinto, Nícolas de Castro Campos; de Oliveira, Luiz Gustavo; Rodrigues, Matheus Nehrer; Aragão, Danielle Maria de Oliveira; Aguiar, Jair Adriano Kopke de; Alves, Maria Silvana; Castañon, Maria Christina Nogueira Marques; Ribeiro, Antônia; Scio, Elita
Abstract: Ethnopharmacological relevance: Vernonia condensata Baker (Asteraceae) is traditionally used in South American Countries as an anti-inflammatory, analgesic and hepatoprotective. Aim of the study: This study aimed to investigate the in vivo hepatoprotective and antioxidant, and the in vitro anti-inflammatory activities of the ethyl acetate partition (EAP) from the ethanolic extract of this medicinal plant leaves. Materials and methods: For the in vivo hepatoprotective activity, rats were pretreated orally for seven days with vehicle, silymarin 100 mg/kg or EAP 50, 100 and 200 mg/kg. Then, acetaminophen 3 g/kg was also orally administrated. Animals were euthanatized 24 h after the damage inducement. The levels of the serum enzymes ALT, AST and ALP were determined, as well as the triglycerides, total cholesterol and fractions. The antioxidant activity was evaluated by TBARS assay and by the measurement of glutathione reductase, superoxide dismutase and catalase activities in the rats liver tissue. The in vitro anti-inflammatory assay using Raw 264.7 cell line induced by lipopolysaccharide was conducted to verify EAP ability to inhibit pro-inflammatory cytokines. Results: EAP was able to inhibit all the acute biochemical alterations caused by acetaminophen overdose. EAP inhibited malondialdehyde formation, maintained the catalase and increased the glutathione reductase activities. Also, EAP decreased NO, IL-6 and TNF-α levels at concentrations from 10 to 20 µg/mL. 1, 5-dicaffeoylquinic acid was isolated and identified as the major compound in EAP. Apigenin, luteolin, chlorogenic acid were also identified. EAP anti-inflammatory action may be due to its antioxidant activity or its capacity to inhibit the pro-inflammatory cytokines. Conclusion: These results strongly suggested that V. condensata may be useful as a possible therapy against liver damage. Graphical Abstract: